The Natural History of Medial Meniscal Root Tears: A Biomechanical and Clinical Case Perspective - Floyd, Edward R.; Rodriguez, Ariel N.; Falaas, Kari L.; Carlson, Gregory B.; Chahla, Jorge; Geeslin, Andrew G.; LaPrade, Robert F. (Frontiers in Bioengineering and Biotechnology, 2021)
Posterior medial meniscus root tears (PMMRTs) make up a significant proportion of all meniscus pathology, and have been definitively linked to the progression of osteoarthritis (OA). A posterior medial meniscus root tear (PMMRT) leads to a increases in average contact pressure in the medial compartment, along with increases in peak contact pressure and a decrease in contact area relative to the intact state. Loss of the root attachment impairs the function of the entire meniscus and leads to meniscal extrusion, thus impairing the force-dissipating role of the meniscus. Anatomic meniscus root repairs with a transtibial pullout technique have been shown biomechanically to restore mean and peak contact pressures in the medial compartment. However, nonanatomic root repairs have been reported to be ineffective at restoring joint pressures back to normal. Meniscal extrusion is often a consequence of nonanatomic repair, and is correlated with progression of OA. In this study, the authors will describe the biomechanical basis of the natural history of medial meniscal root tears and will support the biomechanical studies with a case series including patients that either underwent non-operative treatment (5 patients) or non-anatomic repair of their medial meniscal root tears (6 patients). Using measurements derived from axial MRI, the authors will detail the distance from native root attachment center of the non-anatomic tunnels, and discuss the ongoing symptoms of those patients. Imaging and OA progression among patients who were treated nonoperatively before presentation to the authors will be discussed as well. The case series thus presented will illustrate the natural history of meniscal root tears, the consequences of non-anatomic repair, and the findings of symptomatic meniscal extrusion associated with a non-anatomic repair position of the meniscus.